2008
DOI: 10.5194/acp-8-1547-2008
|View full text |Cite
|
Sign up to set email alerts
|

The atmospheric chemistry of sulphuryl fluoride, SO<sub>2</sub>F<sub>2</sub>

Abstract: Abstract.The atmospheric chemistry of sulphuryl fluoride, SO 2 F 2 , was investigated in a series of laboratory studies.A competitive rate method, using pulsed laser photolysis (PLP) to generate O( 1 D) coupled to detection of OH by laser induced fluorescence (LIF), was used to determine the overall rate coefficient for the reaction O( 1 D)+SO 2 F 2 →products (R1) of k 1 (220-300 K) = (1.3±0.2) × 10 −10 cm 3 molecule −1 s −1 . Monitoring the O( 3 P) product (R1a) enabled the contribution (α) of the physical qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
30
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 21 publications
(27 reference statements)
6
30
0
1
Order By: Relevance
“…For the Oð 1 DÞ þ SO 2 F 2 reaction, the identity of the sulfur-containing products remains a mystery. FTIR observations by Dillon et al (7) showed no evidence for production of SO 2 or SOF 2 . Dillon et al did observe slow secondary production of OH following 248 nm LFP of O 3 ∕SO 2 F 2 ∕H 2 O∕He mixtures, which they postulate as resulting from reaction of F atoms with H 2 O, with the F atoms generated from Oð 1 DÞ þ SO 2 F 2 with a yield of ∼0.2.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…For the Oð 1 DÞ þ SO 2 F 2 reaction, the identity of the sulfur-containing products remains a mystery. FTIR observations by Dillon et al (7) showed no evidence for production of SO 2 or SOF 2 . Dillon et al did observe slow secondary production of OH following 248 nm LFP of O 3 ∕SO 2 F 2 ∕H 2 O∕He mixtures, which they postulate as resulting from reaction of F atoms with H 2 O, with the F atoms generated from Oð 1 DÞ þ SO 2 F 2 with a yield of ∼0.2.…”
Section: Resultsmentioning
confidence: 95%
“…The only published kinetics study of the Oð 1 DÞ þ SO 2 F 2 reaction was recently reported by Dillon et al (7). To measure k 1 ðTÞ, Dillon et al monitored the temporal behavior of OH produced via Oð 1 DÞ reaction with RH (RH ¼ n-C 5 H 12 , n-C 6 H 14 , or H 2 O) in O 3 ∕RH∕SO 2 F 2 ∕He mixtures; they report a temperature-independent (220-300 K) value for k 1 of ð1.3 AE 0.2Þ × 10 −10 cm 3 molecule −1 s −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, rate coefficients, k, for the SO 2 F 2 gas-phase reactions OH + SO 2 F 2 f products (1) and O 3 + SO 2 F 2 f products (2) were reported to be k 1 (294 K) < 1 × 10 -15 cm 3 molecule -1 s -1 and k 2 (294 K) < 1 × 10 -23 cm 3 molecule -1 s -1 . 4 The reported upper limit for the O 3 rate coefficient establishes that this reaction represents a negligible atmospheric loss process for SO 2 F 2 . The upper limit for k 1 , however, corresponds to an atmospheric lifetime for reaction with OH, τ OH , of ∼30 years, and hence, reaction 1 could be a significant atmospheric loss process for SO 2 F 2 .…”
Section: Introductionmentioning
confidence: 92%
“…Cl + SO 2 F 2 f products (4) We also have studied the UV photolysis SO 2 F 2 by measuring its absorption cross section at 184. 9,193, and 214 nm and its photolysis quantum yield at 193 nm.…”
Section: Introductionmentioning
confidence: 99%